ANALISIS PENGUKURAN USABILITY MENGGUNAKAN SYSTEM USABILITY SCALE DAN DISCOVERY PROTOTYPING PADA APLIKASI SIMLITABMAS UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAKARTA - Rama Gio Gustio Fany (2023)
The computerization method in the modern era forces all the work that humans do to use information technology so as not to be left behind by the rapid development of the modern technological era. The use of application technology as a form of computerization of work every day greatly affects the results of work done using technology. Therefore, user satisfaction is an important point in the business process of a system, so the author conducts research on usability calculations on UPNVJ's Simlitabmas application with the aim of measuring the level of usability of the Simlitabmas system. In this research, the author will use the System Usability Scale method using a total of 10 questionnaire questions. The questionnaire was distributed to Simlitabmas application users, namely UPNVJ lecturers with a total of 115 respondents. At the end of the research, it can be concluded that the usability value of the Simlitabmas system using the SUS method obtained a value of 55.89, with a range of results at marginal low, adjective rating range at "OK", and Curved Grading Scale range at "D".